Concise Review: Dental Pulp Stem Cells: A Novel Cell Therapy for Retinal and Central Nervous System Repair. (16th June 2016) - Mead, Ben; Logan, Ann; Berry, Martin; Leadbeater, Wendy; Scheven, Ben A.
Abstract : Dental pulp stem cells (DPSC) are neural crest-derived ecto-mesenchymal stem cells that can relatively easily and non-invasively be isolated from the dental pulp of extracted postnatal and adult teeth. Accumulating evidence suggests that DPSC have great promise as a cellular therapy for central nervous system (CNS) and retinal injury and disease. The mode of action by which DPSC confer therapeutic benefit may comprise multiple pathways, in particular, paracrine-mediated processes which involve a wide array of secreted trophic factors and is increasingly regarded as the principal predominant mechanism. In this concise review, we present the current evidence for the use of DPSC to repair CNS damage, including recent findings on retinal ganglion cell neuroprotection and regeneration in optic nerve injury and glaucoma.